PRODUTIVIDADE DA CULTURA DO MILHO DOCE EM FUNÇÃO DA PROFUNDIDADE DE SEMEADURA E ADUBAÇÃO EM COBERTURA. - GOMIDES, João Flávio Floriano Borges1 (joaoflavio-floriano@hotmail.com); MARTINS, Murilo Battistuzzi² (mbm_martins@hotmail.com; SERON, Cássio de Castro; VENDRUSCOLO, Eduardo Pradi; DOMINGUES, Elyan Carlos da Silva; JÚNNYOR, Wellingthon da Silva Guimarães (ANAIS DO ENIC, 2023)
-